Հարկային կառավարման հիմնախնդիրները փոքր և միջին ձեռնարկատիրության ոլորտում - Մ. Ա. Բեգլարյան (ՀՀ ԳԱԱ հրատ.)
Налоговое бремя МСП в 2014-2016 гг. возросло с 15,2% до 21,7%. При этом для микропредприятий оно составляет 15,5%, для малых -18,7% и 29,8% - для средних, что может ограничить свободу управленческих решений. Налоговое планирование зависит от выбора места регистрации, использования преимуществ налогового законодательства и налоговых льгот, упрощенных налоговых и специальных режимов, организационно-правовой структуры и реализации экономически обоснованной стратегии восстановления налоговых прав. The analysis presented in the article shows that the tax burden of SMEs in 2014-2016 increased from 15.2% to 21.7%. At the same time, the tax burden differs significantly depending on the size of the organization, amounting to 15.5% for micro, 18.7% for small and 29.8% for medium-sized organizations, which may limit the freedom of management decisions. Some areas of tax planning have been identified: the choice of the place of registration, the use of the advantages of tax legislation and tax benefits, simplified tax and special regimes, the organizational and legal structure, and the implementation of an economically feasible strategy for restoring tax rights.
Keywords: H Social Sciences; HRT Revenue; Taxation; Internal Revenue